Thermal characterization and ventilation assessment of a battery-caged laying hen housing in the humid tropic climate - Jongbo, Ayoola Olawole (2024)
The indoor climate to which livestock are exposed is a critical factor influencing their performance and productivity. Elevated air temperature and relative humidity could result in heat stress for laying hens. This situation results in severe adverse effects such as weight loss and mortality. Egg fertility and hatchability are also impacted. Consequently, a study was carried out in a naturally ventilated battery-caged laying hen house to measure climatic variables (air temperature, relative humidity and air velocity). The degree of heat stress was assessed using the temperature-humidity index (THI), and the index of temperature and air velocity (ITV) was also evaluated. According to the results obtained, birds reared within the study building would spend most of their productive life under stressful thermal conditions, which could significantly hamper their performance. The air velocity was below 1.0 ms−1 for most of the internal part of the housing, meaning natural air movement at the location was insufficient to provide a suitable environment for the birds. A high THI was recorded for nearly the entire study period. This high THI could indicate high relative humidity about air temperature. The observed ITV values (ITV > 25) suggest that birds throughout the building could be perpetually uncomfortable. The thermal and velocity profile within the structure could further be assessed numerically using computational fluid dynamics. This would enable engineers to make modifications to improve living conditions within the building.